Nanoparticles Containing Hyaluronan Acid and Astragalus Polysaccharides for Treating Osteoarthritis - Gongbiao Lu; Lin Du; Jishou Lu; Liuzhong Jin (International Journal of Polymer Science)
The pathogeny of osteoarthritis (OA) is very complicated and still is one of the difficulties in a treating procedure. Here, we constructed nanoparticles using hyaluronan acid (HA) and astragalus polysaccharides (APS) for OA therapy. We assessed OA biomarkers and IL-1β-induced matrix metalloproteinase (MMP) expressions. Nanoparticles of 100 nm showed high drug loading of 28.6% (w/w) and extended drug release of 59% over 1 month. Our results demonstrated that nano treatment significantly improved IL-1β-induced cell viability of chondrocytes. Induction of MMP-9, MMP-13, and TNF-α was alleviated by nanoparticles. Furthermore, nano elevated the expression of osteopontin (OPN) and attenuated inducible nitric oxide synthase (iNOS) protein. Our data indicated the protective role of HA and APS-capsuled nanoparticles in OA treatment.